2017 IEEE 18th International Workshop on Signal Processing Advances in Wireless Communications (SPAWC) 2017
DOI: 10.1109/spawc.2017.8227765
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning based channel modeling for molecular MIMO communications

Abstract: In diffusion-based molecular communication, information particles locomote via a diffusion process, characterized by random movement and heavy tail distribution for the random arrival time. As a result, the molecular communication shows lower transmission rates. To compensate for such low rates, researchers have recently proposed the molecular multiple-input multiple-output (MIMO) technique. Although channel models exist for single-input single-output (SISO) systems for some simple environments, extending the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 16 publications
0
41
0
Order By: Relevance
“…The analysis and simulation results have shown that the performance of ligand-receptor reversible binding based DF relay MC can be significantly improved by increasing the ratio of association to dissociation, optimizing the number of molecules distribution scheme, or assigning an optimal location of relay node. In the future, the machine learning can be used for the channel [9], and some new performance metrics can be researched in the DF relay MC systems.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The analysis and simulation results have shown that the performance of ligand-receptor reversible binding based DF relay MC can be significantly improved by increasing the ratio of association to dissociation, optimizing the number of molecules distribution scheme, or assigning an optimal location of relay node. In the future, the machine learning can be used for the channel [9], and some new performance metrics can be researched in the DF relay MC systems.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…represents the probability of a single molecule that was emitted from the ith transmit antenna arriving at the j th receiver antenna at the kth time slot. Due to the presence absorbing receivers, p i j [fc] need to be found by random walkbased Monte Carlo simulations or with the help of artificial neural networks [14]. In this paper, random walk-based Monte Carlo simulations are utilized to generate Pi,j[k].…”
Section: Pi J [K]mentioning
confidence: 99%
“…For modeling a molecular MIMO channel, we utilized the trained ANN of our previous work [22]. A trained ANN is able to estimate the channel coefficients h ji [ ] for a given MIMO scenario without running simulations.…”
Section: Ann For Channel Modelingmentioning
confidence: 99%